The cultural history of plants - Prance, Ghillean T., 1937-; Nesbitt, Mark (Routledge, 2005)
This valuable reference will be useful for both scholars and general readers. It is both botanical and cultural, describing the role of plant in social life, regional customs, the arts, natural and covers all aspects of plant cultivation and migration and covers all aspects of plant cultivation and migration. The text includes an explanation of plant names and a list of general references on the history of useful plants.